Left-Turning Vehicle Trajectory Modeling and Guide Line Setting at the Intersection - Fulu Wei; Weiwei Guo; Xin Liu; Chunyan Liang; Tianjun Feng (Discrete Dynamics in Nature and Society)
When left-turning vehicles are released from the multiple left-turning lanes at the signalized intersection, there will be conflicts among them, and the conflicts will affect the traffic operation and safety. In order to solve the problem, by extracting running trajectories of left-turning vehicles and analyzing distribution characteristics of trajectories, velocity changing characteristics, and flow changing characteristics, the left-turning vehicle’s trajectory model was established. On the basis of the above research, taking an example of quadruple left-turning lanes, the idea of setting left-turning guide line at the intersection was proposed. Through instance verification, we could get the conclusion that the method of using left-turning guide line to control vehicles’ turning process can effectively reduce traffic conflicts and delay and improve traffic efficiency.